2012
DOI: 10.1002/tie.21486
|View full text |Cite
|
Sign up to set email alerts
|

Exploring children, family, and consumption behavior: Empirical evidence from Nigeria

Abstract: Multinational enterprises, especially those in the fast‐moving consumer goods market, have long been concerned with the dynamics of family‐oriented consumption behavior. What is little known is the changing locus of power as children assume more power in family buying decisions. This paper adopts qualitative methods to address the changing role of children, strategies applied to influence family purchases, cultural shifts, and the implications for international business. Nigeria is used as a contextual base bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…They have more autonomy as they can select products on their own and sometimes spend their own pocket money without being supervised. They can also accompany their parents on a collaborative shopping trip, using various tactics to influence them (Nadeau and Bradley, 2012;Gbadamosi, 2012;Darian, 1998 (Girl,9) Choice of products: Variety/abundance is considered by 6-8 year-olds as one of the main advantages of in-store shopping:…”
Section: The Store As a Sales Channelmentioning
confidence: 99%
“…They have more autonomy as they can select products on their own and sometimes spend their own pocket money without being supervised. They can also accompany their parents on a collaborative shopping trip, using various tactics to influence them (Nadeau and Bradley, 2012;Gbadamosi, 2012;Darian, 1998 (Girl,9) Choice of products: Variety/abundance is considered by 6-8 year-olds as one of the main advantages of in-store shopping:…”
Section: The Store As a Sales Channelmentioning
confidence: 99%
“…A fundamental and crucial phenomenon in marketing and consumer behavior is the family as a customer and decision-making unit (Gbadamosi, 2012). Its value as a unit of analysis in consumer purchasing decisions is widely established (Xia et al, 2006).…”
Section: Family Buying Decisionsmentioning
confidence: 99%
“…Wimalasiri , (2004) found that older children resort to rational persuasion than their younger counterparts because they try to justify their opinion or request by using some sort of factual evidence like television and radio advertisements. But Gbadamosi, (2012) claimed that Nigerian children start to request any good and service through direct request; if a direct request fails, a child would resort to the use of persuasion, and if that does not yield the expected result, the child resorts to the emotional tactic, with reference to the other.…”
Section: Children's Negotiation Strategies In Family Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some studies have cautioned on this postulation indicating that children could also make decisions in some circumstances. A good example here is the study of Gbadamosi (2012) who argues that children in Nigeria, especially in cosmopolitan cities, are sometimes given free will to choose when the products involved are routinely consumed items such as snacks. Similarly, the notion of e-shopping also creates a twist to the issues of purchase decisions.…”
Section: Consumer Decision-making Process: Emerging Issuesmentioning
confidence: 99%